2021
DOI: 10.1186/s12877-021-02390-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of tai chi exercise on functional fitness in community-dwelling older adults with mild degenerative knee osteoarthritis: a randomized controlled clinical trial

Abstract: Background Degenerative osteoarthritis (OA) often leads to pain and stiffness of the affected joints, which may affect the physical performance and decrease the quality of life of people with degenerative knee OA. Compared to traditional exercise, tai chi is a safe exercise with slow movements which can facilitate physical functioning and psychological well being, and might be suitable for improving the physical activities of older adults with knee OA. Therefore, this study investigated the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…Therefore, the development of an appropriate exercise with low joint impacts and loading of OA knee joints is critical for improving the muscle strength and function in the lower limbs of older adults with knee OA. The results of numerous studies are consistent with these findings [17,18].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the development of an appropriate exercise with low joint impacts and loading of OA knee joints is critical for improving the muscle strength and function in the lower limbs of older adults with knee OA. The results of numerous studies are consistent with these findings [17,18].…”
Section: Introductionsupporting
confidence: 76%
“…Recent studies reported that Tai Chi exercises are safe and slow movement multicomponent exercises with low impacts on the OA knee joint in older adults [18,19], and they improve physical performance, functional fitness, and psychological health conditions in older adults [18,[20][21][22][23]. Although Tai Chi can significantly improve physical performance and reduce pain and stiffness in individuals with OA [18,22,23], several limitations were also reported, including the requirement of well-experienced Tai Chi exercise instructor, inadequate feedback in group exercises, being insufficiently challenging, and high withdrawal rate because of boredom [18,24]. By contrast, combining game-based feedback and exercise can considerably enhance motivation, muscle strength, range of motion, and adhesion for people with knee disorders [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Its effect mainly relieves OA symptoms and delays cartilage wear ( Yao et al, 2021 ); it also has the advantages of a stable curative effect, low cost, and small side effects. In addition to internal and external administration of Chinese medicine, effective treatments of OA have been reported for needle therapy ( Mao and Kapur, 2010 ; Fu et al, 2020 ), moxibustion ( Wang et al, 2020 ), Tai chi ( Chen et al, 2021 ; Zheng et al, 2021 ), baduanjin ( Li J et al, 2020 ), and other non-drug treatments ( Song et al, 2021 ). However, insignificant effects over the corresponding placebo have been reported in reducing pain or improving function in patients with KOA ( Lao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with OA of the knee, loss of movement and function might limit their day-to-day activities, such as stair climbing, walking, and doing household chores. These conditions might diminish the patients’ quality of life and might be associated with depression and disturbed sleep, which additionally contribute to disability [ 44 , 45 ]. Previous research showed a significant negative association between social support and the prevalence of depression among the elderly [ 46 ].…”
Section: Discussionmentioning
confidence: 99%